Acute Toxicity Studies of Brucea javanica Merril Leaves Extract on Mice - Marissa Angelina; Indah D Dewijanti; Banjarnahor S D S; Megawati megawati; Tri Yuliani (Journal of Tropical Life Science, 2012)
The objective of the study was to evaluate the oral acute toxicity of Brucea javanica Merril extract on both Male and Female DDY-Mice. Brucea javanica leaves have activity as a cytotoxic, anti-diarhhea, etc. Brucea javanica leaves extract was administered orally for first 24 hours at various dose levels (562.5mg/kg bw, 1125 mg/kg bw, 2250 mg/kg bw, and 4500 mg/kg bw) to determine the toxicity effects. The treatment groups were compared to the normal control. Vital organs (liver, heart, lymph, lungs, etc) and body weight were analyzed to study the toxicity. LD50 determined using Reed and Munich formula. Vital organs average weight showed no difference between control group and treatment groups from the lowest dose until the highest dose. In addition, the body weight data showed no difference between control group and treatment groups. LD50 for Brucea javanica extract using Reed and Munich formula was 1003.65 mg/kg bw. The result of the study showed that extract were categorized as lightly toxic.Keywords: Acute toxicity, Brucea javanica Merril, DDY-Mice, LD50